History of Recurrent Implantation Failure is Associated With the Incidence of Adverse Perinatal Outcomes in Singleton Live Births Following Frozen-Thawed Embryo Transfer Cycles - Li, Na; Guan, Yichun; Liu, Junjie; Ren, Bingnan; Du, Yulin; Wang, Kexin; Zhang, Yongjie; Lou, Hua (Frontiers in Endocrinology, 2022)
Objective: To investigate whether patients with a history of recurrent implantation failure (RIF) are associated with adverse perinatal outcomes in singleton live births following frozen-thawed embryo transfer (FET) cycles. Design: Retrospective cohort study. Methods: This study analyzed the obstetric and neonatal outcomes of patients with and without a history of RIF who underwent FET cycles in a single reproductive center between January 2017 and October 2020. A total of 1100 women with singleton live births beyond 28 weeks of gestation were included. The primary outcome measures were perinatal outcomes, especially gestational age, birthweight, preterm birth (PTB), large for gestational age (LGA), small for gestational age (SGA), congenital malformation rates, and premature rupture of the membranes (PROM). Multiple logistic regression was used to establish relationships between RIF and adverse perinatal outcomes after adjusting for relevant baseline demographics and cycle characteristics. Result(s): The RIF group showed a preferred transfer of two embryos and cleavage embryos compared with the control group (P<0.05). Regarding perinatal outcomes in singleton deliveries, women with RIF had increased rates of LBW (adjusted odds ratio [aOR] 2.027; 95% confidence interval [CI], 1.025~4.009), PTB (aOR 1.785; 95% CI, 1.050~3.036), and PROM (aOR 2.259; 95% CI, 1.142~4.467). The incidence of congenital malformations was similar between the two groups (4.1% vs. 2.4%; P = 0.759). Furthermore, multiple intrauterine procedures were associated with a statistically significant increased risk of PROM in RIF patients (aOR 1.537; 95% CI, 1.105~2.137). Conclusions: Women with a history of RIF were associated with an increased risk of LBW, PTB, and PROM in singleton live births after FET cycles. In addition, multiple intrauterine procedures were independent risk factors for PROM.